2011
DOI: 10.1183/09031936.00173710
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Global Initiative for Asthma (GINA) criteria with the Childhood Asthma Control Test (C-ACT) and Asthma Control Test (ACT)

Abstract: Several tools are useful in detecting uncontrolled asthma in children. The aim of this study was to compare Global Initiative for Asthma (GINA) guidelines with the Childhood Asthma Control Test (C-ACT) and the Asthma Control Test (ACT) in detecting uncontrolled asthma in children.145 children with asthma filled in a web-based daily diary card for 4 weeks on symptoms, use of rescue medication and limitations of activities, followed by either the C-ACT or ACT. For predicting uncontrolled asthma, score cut-off po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 25 publications
1
74
1
2
Order By: Relevance
“…A recent study showed that a cutoff score of 12 for the C-ACT can identify children with very poorly controlled asthma (22). Another study comparing C-ACT scores and asthma control levels based on the GINA criteria found that a cutoff score of 19 resulted in a high specificity (100%) but a low sensitivity (33%) for detecting children with uncontrolled asthma (23). Using each cutoff score adequately might help clinicians to optimize asthma therapy.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study showed that a cutoff score of 12 for the C-ACT can identify children with very poorly controlled asthma (22). Another study comparing C-ACT scores and asthma control levels based on the GINA criteria found that a cutoff score of 19 resulted in a high specificity (100%) but a low sensitivity (33%) for detecting children with uncontrolled asthma (23). Using each cutoff score adequately might help clinicians to optimize asthma therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Although a single numerical value to express asthma control is highly attractive, C-ACT, ACT and ACQ do not include exacerbations and future risks, such as lung function decline [66][67][68][69]. Therefore, these composite scores appear to underestimate the level of asthma control as defined by GINA [70]. Recently, two composite asthma control scores have been developed that include exacerbations: the Test for Respiratory and Asthma Control in Kids (TRACK) and the Composite Asthma Severity Index (CASI) [71,72].…”
Section: Clinical Tools: Symptoms Exacerbations and Qolmentioning
confidence: 99%
“…Possible treatment options for school aged children with severe asthma The purpose of pediatric asthma treatment for the child is to control symptoms, to be able to lead a normally active life, to have normal lung function and to prevent asthma exacerbations [86,87]. A stepwise therapeutic approach is applied where medications are adjusted depending on symptom and several guidelines have been published to support the physician in these treatment decisions [4, [87][88][89][90][91].…”
Section: Assessment Of Inflammationmentioning
confidence: 99%